PENGUATAN NUMERASI SISWA SEKOLAH DASAR: IMPLEMENTASI MEDIA MATH PLAYGROUND PADA SISWA SANGGAR BIMBINGAN KEPONG MALAYSIA - suharyanto, novitafebriyani; Oman Hadiana; Casnan; Tio Heriyana; Hana Astria Nur (PGSD Universitas Muhammadiyah Cirebon, 2025)
This study aims to improve students' numeracy skills by using technology-based learning media Math Playground. In this study, quantitative research is used which aims to test the hypothesis of the data that has been collected in accordance with previous theories and concepts. The method used is a quasi-experimental experiment, namely experimental research carried out on one group only without a comparison group or control group (One group pre-test and post-test). The research sample consisted of 10 students of Sanggar Bimbingan Kepong Malaysia. The instrument used was a numeracy test for elementary school students. The data analysis technique used was the T-test statistical test. The results of the study showed that numeracy skills which were initially low, by implementing learning media in the form of a math playground website can help improve students' numeracy skills. This shows that there has been a significant increase seen from the test results in the form of pre-tests and post-tests given to students. To improve and also develop media in the form of math playgrounds, further research is expected to be able to conduct research with a longer period of time. This needs to be done so that researchers can observe how students' numeracy skills develop if over time in the long term (comparison). Keywords: Learning Media, Numeracy, Math Playground, Technology